Co-delivery of Bmi1 small interfering RNA with ursolic acid by folate receptor-targeted cationic liposomes enhances anti-tumor activity of ursolic acid in vitro and in vivo - Weijie Li; Ruicong Yan; Yong Liu; Chuanchuan He; Xiaojuan Zhang; Yao Lu; Muhammad Waseem Khan; Chuanrui Xu; Tan Yang; Guangya Xiang (Taylor & Francis Group, 2019)
Overexpression of Bmi1 gene is an important feature of cancer stem cell in various human tumors. Therefore, Bmi1 gene can be a potential target for small interfering RNA (siRNA) mediated cancer therapy. Ursolic acid (UA) as a natural product plays a pivotal role in anti-tumor field, although its performance is limited by low bioavailability and poor hydrophilicity. A folate receptor-targeted cationic liposome system was designed for the purpose of investigating the relationship between Bmil siRNA and UA. The folate receptor-targeted cationic liposomes co-delivering UA and Bmi1 siRNA (FA-UA/siRNA-L) were fabricated by electrostatic interaction between folate UA liposome (FA-UA-L) and Bmi1 siRNA. Tumor growth is inhibited by FA-UA/siRNA-L in vitro and in vivo and this inhibition is contributed by a synergistic anti-tumor effect of UA and Bmi1 siRNA. The western blot measurement of apoptosis-protein and cancer stem cell (CSC) marked-protein demonstrated that UA led to activation-induced tumor cell death and Bmi1 siRNA resulted in inhibition of cancer stem cells. Overall, these results indicate that Bmi1 as a regulating gene for cancer stem cell is an effective target for cancer treatment using siRNA and co-delivery of UA and Bmi1 siRNA using folate-targeted liposomes is a promising strategy for improved anti-tumor effect.